The Syrian regime’s resilience through the prism of its struggle for (re)consolidation of the state - Μητρούσης, Ηλίας (Πανεπιστήμιο Πελοποννήσου, 2020)
This thesis deals with the resilience of President Bashar al-Assad's regime since the beginning of the Syrian uprising in 2011 and aims to explore the internal factors that helped it cling to power. To that end, the thesis inquires into the leading military and political strategies the regime formulated and implemented in order to cope with the immense ideological, military and institutional challenges to its survival. However, since the name Assad had already shaped the regime -and the country- long before the Bashar inherited the Presidency, this study of contemporary events, cannot but take into account Hafez al-Assad’s contribution to the regime’s long history of consolidation in Syria. Bashar al-Assad ‘inherited’ a stable country, where the ideology of his regime was the ideology of the state, and the state institutions have been adjusted to serve the regime’s prerogatives and longevity. The Syrian uprising of 2011 and the civil war that followed though, put the regime’s ‘state’ into jeopardy, and along with it the regime itself. In this very context, Bashar al-Assad’s regime inextricably tied its survival with that of the state and took pains to strategize accordingly, in order to reassert itself as the only viable and capable entity to govern Syria
Keywords: Συρία--Πολιτική και διακυβέρνηση; Συρία--Κοινωνικές συνθήκες; Συρία--Πολιτικές συνθήκες; Συρία--Στρατιωτική πολιτική; Συρία--Εξωτερικές σχέσεις; Συρία; Συριακό Καθεστώς; Ασφάλεια Καθεστώτος; Συριακή εξέγερση